The relationship between time anxiety and college students’ sleep quality: the mediating role of irrational procrastination and the moderating effect of physical activity - Sun, Zhe; Gao, Xinchao; Ren, Penghui (Frontiers in Psychology, 2024)
Background Poor sleep quality has become one of the most pressing public issues among Chinese college students, with an increasing incidence rate in recent years. Although some studies showed that anxiety is related to sleep quality, the relationship between time anxiety (which is a more concrete manifestation of anxiety in the temporal dimension) and sleep quality, as well as its potential mechanisms, still requires further investigation and analysis. This study aimed to explore the relationship between time anxiety and sleep quality among college students, and to examine the mediating role of irrational procrastination and the moderating effect of physical activity. Methodology A cross-sectional study was conducted with 1,137 participants recruited from four universities in eastern, western, and central China. They completed a questionnaire survey on time anxiety, irrational procrastination, physical activity, and sleep quality. Data analysis was performed using SPSS 26.0 and PROCESS 3.3. Results Time anxiety had a significant positive impact on sleep quality (β = 0.28, t = 9.95, p < 0.001). Irrational procrastination played a mediating role between time anxiety and college students’ sleep quality, the effect value was 0.05, and the intermediary effect accounted for 19.26%. Physical activity moderated the direct effect of time anxiety on college students’ sleep quality (β = −0.08, t = −2.98, p < 0.01), and moderated the second half path of irrational procrastination mediation model (β = −0.06, t = −2.12, p < 0.05). Conclusion Higher levels of time anxiety are associated with poorer sleep quality among college students. Time anxiety not only directly affects college students’ sleep quality, but also indirectly affects it through irrational procrastination. Conducting physical activities can mitigate the impact of time anxiety and irrational procrastination on college students’ sleep quality.